Lean Brain Management More Success and Efficiency by Saving Intelligence - Dueck, Gunter. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Intelligence is wasted on problems that themselves have been caused by an excess of intelligence. Lean Brain Management strives toward uncompromising Lean Brain Quality. Lean Brain stands for consistent economization of intelligence in all realms of life: Intelligent systems will only be operated by unskilled workers. Education, universities, and schools would become obsolete. A week of training would be enough for virtually any job. ("You are now the physician for the measles in the State of Ohio. In response to phone calls, send this prescription.") Lean Brain is not aimed at dumbing down! Lean Brain can survive on just a very small amount of central intelligence. Potential savings amount to trillions! This is demonstrated using Germany as an example. With this book, Dueck presents a radical suggestion for world improvement. The desire to laugh infinitely about it will eventually segue into a collective rude awakening. The book contains concrete advice for managers to economize on intelligence, and is thus—in keeping with the theme—written in an easy-to-read fashion. It contains no self-doubt whatsoever. Awarded the Business Book Prize from Financial Times Deutschland and getAbstract AG.